Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Wordwall terhadap Keterampilan Berpikir Kritis Siswa pada Mata Pelajaran IPA di Kelas VII SMP Negeri 6 Samarinda - Triana Adawiyah; Akhmad Akhmad; Sonja Verra Tinneke Lumowa; Vandalita Maria Magdalena Rambitan; Masitah Masitah; Lilis Suryani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This research is motivated by the lack of application of varied learning models, causing low critical thinking skills of students in science learning, so the Problem Based Learning (PBL) model assisted by wordwall is used as a solution. This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by wordwall media on critical thinking skills of seventh grade students of SMP Negeri 6 Samarinda. This research is a quantitative study using a quasi-experimental method with a non-equivalent control group design. The research sample consisted of classes VII C (experimental) and VII D (control), each with 21 students. Data analysis was carried out through normality tests, homogeneity tests, independent sample t-tests and N-Gain tests using SPSS version 25 data processing tools. The results showed a significant difference between the two classes (p = 0.001 < 0.05). The average N-Gain of the experimental class was 0.549 (medium category), higher than the control class of 0.281 (low category). These findings indicate that the implementation of problem-based learning assisted by word walls effectively improves students' critical thinking skills in science learning.